Pengaruh Model Pembelajaran Problem Based Instruction (PBI) terhadap Pengetahuan dan Sikap Remaja tentang HIV/AIDS di SMP Achmad Jani Puger Kabupaten Jember (The Effect of Model Learning: Problem Based Instruction (PBI) towards Knowledge and Attitude of - Dicky Andriansyah; Rondhianto Rondhianto; Ahmad Rifai (Pustaka Kesehatan, 2016)
AIDS remains ranked as the third most deadly disease in Indonesia. The disease is caused by the HIV that can lead to lower a person's immune status to trigger an opportunistic infections and cause of death. The incidence of HIV disease in 2014 has reached 32,711 cases, at the age of 14-19 years of 1,717 cases (5.24%). Lack of knowledge among teenagers about HIV/AIDS makes their behavior leads to negative interactions or risk to free sex, misuse of syringes, and other related problems. Problem-based instruction (PBI) as a learning model is expected to change knowledge and attitudes of teenagers on HIV / AIDS. The results of dependent t-test t value -3.8380 for knowledge, and the value of t -22.174 for attitudes which means an increase in value after a given model of PBI with a mean difference -6.800 and -24.000 respectively for knowledge and attitudes. The p value 0.000 for the results obtained knowledge and attitudes.The p value was